Nitric Oxide Concentration and Other Salivary Changes after Insertion of New Complete Dentures in Edentulous Subjects. (29th February 2016) - Breseghelo, Maria de Lourdes; Guillo, Lídia Andreu; Nogueira, Túlio Eduardo; Leles, Cláudio Rodrigues
Abstract : Objective . To assess changes in levels of salivary nitric oxide (NO) after insertion of new complete dentures and its association with clinical and salivary parameters. Methods . Nineteen fully edentulous subjects were included, mean age 64.4. Unstimulated whole saliva was collected before and after insertion of the dentures, at follow-up visits, and after 12 months. The concentration of the final stable NO product (nitrite) was measured by a colorimetric assay based on the Griess reaction. Clinical parameters were assessed during all clinical visits. Results . Functional adaptation to the dentures progressively improved, with no complaints at the long-term follow-up. NO concentration was not influenced by the level of functional adaptation, presence of injuries to the mucosa, salivary flow, and saliva viscosity. Pairwise comparison showed a reduction in NO concentration at the first follow-up compared to baseline values but differences were not statistically significant. Significant differences were observed in NO concentrations at the long-term follow-up when compared to the first (p = 0.024 ) and second (p = 0.027 ) visits. Conclusion . NO concentration reduced after denture insertion and returned to baseline levels in the long-term follow-up. This appears to be an autonomic response of the body and provides valuable complementary information for the management of the edentulous patient.